2023
DOI: 10.3389/fcimb.2022.1095053
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine ameliorates experimental autoimmune encephalomyelitis by rebalancing the homeostasis of gut microbiota and reducing blood-brain barrier disruption

Abstract: BackgroundIncreasing evidence suggests that gut dysbiosis can directly or indirectly affect the immune system through the brain-gut axis and play a role in the occurrence and development of Multiple sclerosis (MS). Oxymatrine (OMAT) has been shown to ameliorate the symptoms of MS in the classical experimental autoimmune encephalomyelitis (EAE) model of MS, but whether its therapeutic role is through the correction of gut dysbiosis, is unclear.MethodsThe effects of OMAT on intestinal flora and short-chain fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Recent research even found a link between the development of different T cell subtypes and particular bacterial species. Polysaccharide A (PSA) molecules from Bacteroides fragilis have been found to stimulate the development of a systemic Th1 response [24]. The prevalence of neurodegenerative diseases is currently rising quickly.…”
Section: Impact Of the Gut Microbiota On Physiologymentioning
confidence: 99%
“…Recent research even found a link between the development of different T cell subtypes and particular bacterial species. Polysaccharide A (PSA) molecules from Bacteroides fragilis have been found to stimulate the development of a systemic Th1 response [24]. The prevalence of neurodegenerative diseases is currently rising quickly.…”
Section: Impact Of the Gut Microbiota On Physiologymentioning
confidence: 99%
“…Plant‐derived anthocyanins may prevent cognitive deficit‐related behaviors by correcting dysbiosis, restoring the intestinal ecological and functional microenvironment, and inhibiting inflammation mediated by immune cells 145 . Apart from alleviating cognitive impairment, plant root‐derived oxymatrine may alleviate clinical symptoms and pathological manifestations of multiple sclerosis by correcting microbiota dysbiosis, suppressing immune cell‐mediated inflammation, and remodeling the gut–brain axis 146 . Another natural plant antitoxin, pterostilbene, could reduce the release of inflammatory factors by decreasing lipopolysaccharide levels and modulating TLR4/NF‐κB signaling pathways in the colon and brain, thereby inhibiting oxidative stress damage, astrocyte and microglia activation, and dopaminergic neuron loss 147 .…”
Section: Treatment Of Brain Injury In Preterm Infants Mediated Throug...mentioning
confidence: 99%
“…Oxymatrine Remodel GM homeostasis Decrease BBB permeability, and ameliorate experimental autoimmune encephalomyelitis [146] Pterostilbene Increase the levels of SCFAs and maintain normal intestinal permeability Ameliorate cognitive dysfunction, and improve both memory and learning ability [147] Dimethyl itaconate…”
Section: Drugs Impact On Microbiota Effects Referencesmentioning
confidence: 99%
See 2 more Smart Citations